Pendampingan Kreativitas Santri Melalui Pelatihan Rebana, Kaligrafi, dan Khithobiyah di Pondok Pesantren Sunan Drajat 7 Gesikharjo Palang Tuban - Nurul Fahmi; Erika Rohmawati; Miss Ula Qothifatul Milah (Santri: Journal of Student Engagement, 2023)
Every Islamic Boarding School always has enormous asset potential, as well as the Sunan Drajat 7 Gesikharjo Palang Tuban Islamic Boarding School. Every asset owned, in reality, has not been fully explored and developed as well as possible. Through the discussion forum we can see that the quantity of human resources here is an asset that needs to be developed. Santri who are in this Islamic boarding school have intelligence, creativity and high enthusiasm in studying. In addition to studying religious studies, they must also have expertise in various fields in order to compete globally, both academically and non-academicly. Therefore, it is necessary to assist the creativity of students through various training activities. The purpose of this assistance is (1) To develop the ability of students in the fields of tambourine, calligraphy, and khitobiyah, (2) Introducing good methods and techniques in every training activity. The method used is through the ABCD (Asset Based Community Development) approach. The results of this mentoring show that (1) Santri can play an active role in tambourine, calligraphy, and khithobiyah activities in every event held by Islamic Boarding Schools, (2) Santri can know and apply techniques in tambourine, calligraphy, and khithobiyah activities.